Possible influences of a macroalgal bloom in eelgrass beds on fish assemblages in the lower Knysna Estuary, South Africa. Issue 3 (25th September 2018) - Pollard, M; Whitfield, AK; Hodgson, AN
Abstract : The occurrence of a macroalgal bloom at eelgrass ( Zostera capensis ) sampling sites in the summer of 2014/2015 provided an opportunity to use underwater video cameras to monitor the possible effects of environmental change on fish diversity and abundance in the lower reaches of the Knysna Estuary. A General Linear Model (GLM) showed that there was a significant difference in the abundance of fish before and after an invasion of the sampling sites by the macroalga Ulva lactuca . The eelgrass bed fish abundance was more affected by the macroalgal bloom than the bare substratum fish abundance, with the Ulva impacting negatively on the relative abundance of Mugilidae in the former habitat. The hypothesis that macroalgal invasions have a negative effect on fish diversity and abundance is therefore supported by this preliminary study.